The influence of geographical knowledge networks on innovative performance: evidences from the Hsinchu Science-based Industrial Park, Taiwan. (17th March 2009) - Chang, Yuan-Chieh; Lin, Bou-Wen; Hung, Shih-Chang; Liu, Meng-Chun
This paper examines how geographically inter-organisational networks affect innovative performance of firms located in industrial clusters, especially the Hsinchu Science-based Industrial Park (HSIP) in Taiwan. Based on an exhaustive manual search of the United Daily News Group database, 1445 inter-organisational alliances were identified in the period from 1991 to 2002. This research revealed that the innovation performances of firms in industrial clusters may benefit not only from networking in industrial clusters but also from national and international networking. Policies should encourage industrial clusters to establish symbiotic innovation networks between local, national and global partners.